INFILTRASI DAN LIMPASAN PERMUKAAN PADA POLA TANAM AGROFORESTRI DAN MONOKULTUR : STUDI DI DESA JERU KABUPATEN MALANG - Darmayanti, Agung Sri; Solikin, Solikin (Prosiding Seminar Biologi, 2013)
The  research  aims to determine  rate of water  infiltration and   soil run off  on agroforestry,  parennial  and annual  monoculture  cropping systems was conducted at  Jeru village Malang Refency. The water  infiltration rate was measured  by infiltrometer  and the soil  run off  was measured  simple ranfall simulator to make run off  on the soil.  The run off water and  soil  flowing  was   sheltered  into  a  glass   and   then weighing the dry mass of the soil.  Parameters observed  were plant species, trees architectures model, the amount of litter in the land. The results   showed  that  the  highest  water  infiltration rate  and  the lowest  soil run off  was  on multiculture agroforestry each 63,5 cm.h-1 and 0,3 g.lt-1  whereas  the  lowest  water infiltration  and  the highest  soil run off  was on  perennial  trees monoculture  cropping  system  each 30  h-1 and  2,9 g.lt-1 . The multiculture agroforestry  was  dominated by ?waru  gunung? (Hibiscus macrophyllus), ?mindi? (Melia azedarach), ?mahoni? (Sweitenia macrophylla), bamboes and cassava (Manihot esculenta)  that have different  tree architecture  models.  The diversity of  the tree species also  caused   varying litters  produced.  Key Word : infiltration, run off, architecture, litter